If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5) + 2x = 26 Reorder the terms: (5 + x) + 2x = 26 Remove parenthesis around (5 + x) 5 + x + 2x = 26 Combine like terms: x + 2x = 3x 5 + 3x = 26 Solving 5 + 3x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3x = 26 + -5 Combine like terms: 5 + -5 = 0 0 + 3x = 26 + -5 3x = 26 + -5 Combine like terms: 26 + -5 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| 8h-29=43 | | 6h-12=2h+36 | | -c=c+10 | | x^6=81 | | 10-3b=-10-8b | | 6-4(3x-3)=6 | | -3.5=9.4k+3(-3k-1.7) | | 6(x+5)=7.5 | | 5y-9+y+29=8y+20-4y | | -9-2p=-p | | 5x-9+x+29=8x+20-4x | | 4a^2+15a-25=0 | | 325.8+(-21.13)=114.5 | | 2(x-6)=8(x+3) | | 3(8)-4=12 | | 2(x-8)=8(x+3) | | 2k+9=-7k | | 3x+15=3x-10 | | 2ln(x+1)-1=0 | | -8x-7x=-120 | | -10y-6=-9y | | 7x-12x=-5 | | -4(3x-4)+4=-12x+20 | | 125.7-(-1.82)=1.439 | | -10y-6=-9 | | -7b=35 | | (5x^2y-3xy)+(2x^2y-xy)= | | 6(2a-3)-4=2 | | 8m+9=63 | | 4d-5d=5 | | 0.5x+10=0 | | -75=35 |